2013
DOI: 10.1371/journal.pone.0064723
|View full text |Cite|
|
Sign up to set email alerts
|

Adult Bone Marrow Neural Crest Stem Cells and Mesenchymal Stem Cells Are Not Able to Replace Lost Neurons in Acute MPTP-Lesioned Mice

Abstract: Adult bone marrow stroma contains multipotent stem cells (BMSC) that are a mixed population of mesenchymal and neural-crest derived stem cells. Both cells are endowed with in vitro multi-lineage differentiation abilities, then constituting an attractive and easy-available source of material for cell therapy in neurological disorders. Whereas the in vivo integration and differentiation of BMSC in neurons into the central nervous system is currently matter of debate, we report here that once injected into the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…However, improvement of neurogenic differentiation potential may not have resulted from the proliferation of MSCs transformed directly by gelatin, but rather by neural progenitor cells (NPCs) attached preferentially to gelatin. This possibility is consistent with studies reporting that primary cells isolated from bone marrow include diverse types of cells, such as Fukata et al (2013); Ghosn et al (2012) MSCs (Ben Azouna et al, 2012Takemitsu et al, 2012;Li and Ikehara, 2013), NPCs (Ricciardi et al, 2012;Neirinckx et al, 2013), hematopoietic stem cells (Ghosn et al, 2012;Fukata et al, 2013), and lymphoid progenitor cells (Pang et al, 2011;Anthony and Link, 2014). To definitively establish whether gelatin enhances the neurogenic differentiation potential to MSCs without any proliferation of NPCs among primary cells derived from bone marrow, we characterized the percentages of MSCs and NPCs in primary cells isolated from bone marrow.…”
Section: Introductionsupporting
confidence: 89%
“…However, improvement of neurogenic differentiation potential may not have resulted from the proliferation of MSCs transformed directly by gelatin, but rather by neural progenitor cells (NPCs) attached preferentially to gelatin. This possibility is consistent with studies reporting that primary cells isolated from bone marrow include diverse types of cells, such as Fukata et al (2013); Ghosn et al (2012) MSCs (Ben Azouna et al, 2012Takemitsu et al, 2012;Li and Ikehara, 2013), NPCs (Ricciardi et al, 2012;Neirinckx et al, 2013), hematopoietic stem cells (Ghosn et al, 2012;Fukata et al, 2013), and lymphoid progenitor cells (Pang et al, 2011;Anthony and Link, 2014). To definitively establish whether gelatin enhances the neurogenic differentiation potential to MSCs without any proliferation of NPCs among primary cells derived from bone marrow, we characterized the percentages of MSCs and NPCs in primary cells isolated from bone marrow.…”
Section: Introductionsupporting
confidence: 89%
“…Our group previously reported a complete comparison of bone marrow MSCs and neural crest stem cells (NCSCs), and showed that both cell types were able to give rise to functional neurons in vitro [ 12 ]. Even if those cells failed to differentiate into neurons in experimental models for Parkinson’s disease [ 13 16 ] and other neurological conditions such as SCI [ 1 , 17 , 18 ], BMSCs are still considered as powerful candidates for cell therapy protocols. Indeed, the literature largely associates the positive impact of BMSCs in neurological disorders to their secretome, composed of all the molecules and vesicles secreted by these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Using a lineage-tracing system, rodent neural crest-derived cells were detected in adult tissues such as bone marrow, and still retained multipotent differentiation properties, which indicated that these cells are one of the cell-of-origin of multipotent mesenchymal stromal cells (MSCs) [7] , [8] . Therefore, the production of human MSCs (hMSCs) from hPSCs via NCC lineage is a promising approach for the use of hPSCs in innovative medicine [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%